Dispersion fuel for nuclear research facilities - Kushtym, А.V.; Belash, M.M.; Zigunov, V.V.; Slabospitska, O.O.; Zuyok, V.A. (Вопросы атомной науки и техники, 2017)
Designs and process flow sheets for production of nuclear fuel rod elements and assemblies TVS-ХD with disper-sion composition UO₂+Al are presented. The results of fuel rod thermal calculation applied to Kharkiv subcritical assembly and Kyiv research reactor VVR-M, comparative characteristics of these fuel elements, the results of metal-lographic analyses and corrosion tests of fuel pellets are given in this paper. Представлені конструкції і схеми виготовлення стрижневих твелів і складання ТВЗ-ХД з дисперсійною композицією UO₂+Al. Наведено результати теплового розрахунку твелів стосовно харківської підкритичної установки та київського реактора ВВР-M, їхні порівняльні характеристики, результати металографічних досліджень та корозійних випробувань паливних таблеток. Представлены конструкции и схемы изготовления стержневых твэлов и сборок ТВС-ХД с дисперсионной композицией UO₂+Al. Приведены результаты теплового расчета твэлов применительно к харьковской подкритической установке и киевскому исследовательскому реактору ВВР-М, их сравнительные характеристики, результаты металлографических исследований и коррозионных испытаний топливных таблеток.